Assistance In Brand Design And Product Packaging Of Msmes In Segunung Hamlet, Carang Wulung Village, Wonosalam District - Sumiati, Sumiati; Panjaitan, Hotman (International Journal Of Community Service, 2022)
Packaging and brand design are essential factors that can help MSME businesses compete in an increasingly competitive market. Attractive packaging and brand design can differentiate a product from competitors. For this reason, it is necessary to pay attention to the packaging of MSME products in Segunung Hamlet, Wonosalam sub-district. Community service has been carried out to assess the understanding of MSME entrepreneurs' understanding of the importance of packaging design and product branding in the MSMEs of Dusun Segunung. Mentoring and training are used by choosing one of the superior products, Tahu Walik Shrimp, produced by MSMEs in Segunung Hamlet. The results of community service in packaging design and product branding include shapes, materials, colors, images, and product information. The packaging design changes the old packaging (plastic bags) into new, more attractive packaging, not only to wrap, protect and prolong the life of shrimp tofu but also to identify the brand and differentiate it from other products on the market.